A history of monitoring marine birds at sea in eastern and Arctic Canada - Carina Gjerdrum; David A. Fifield; Francois Bolduc; Sarah N.P. Wong; Matthieu Beaumont; Mark L. Mallory (Arctic Science)
Systematic surveys of marine birds from ships were first conducted by the Canadian Wildlife Service in Atlantic Canada in 1965, and then expanded to the Canadian Arctic in 1969 under PIROP (Programme intégré de recherches sur les oiseaux pélagiques). PIROP surveys ended in 1992, then resumed in 2006 under the Eastern Canada Seabirds at Sea program with an updated survey protocol. Surveys under both monitoring programs were conducted from a variety of ship types engaged in scientific, transport, and supply activities, totalling over 120 000 km within sub-Arctic and Arctic Canada waters and over a million marine birds observed, primarily northern fulmar (Fulmarus glacialis), black-legged kittiwake (Rissa tridactyla), thick-billed murre (Uria lomvia), and dovekie (Alle alle). The data collected inform offshore ecological inquiries, environmental impact reviews, mortality estimates from accidental oil releases, and define areas in need of protection. Although surveys were designed to quantify seabird distribution within the waters of eastern Canada, the data also include sightings of non-avian taxa that are made publicly available. Long-term and large-scale monitoring programs will remain essential for assessing the status and health of Canada's marine birds, including surveys that take place at sea where these species spend most of their time.